(untitled) (Revista de Ciências Agroveterinárias, 2025)
The chemical composition of propolis is highly variable and complex and is related to the phytogeography of a region. Therefore, the ecology of the local flora is directly related to its chemical composition. The aim of this study was to identify the pollen types and chemical substances of hexane extracts present in the propolis of Scaptotrigona nigrohirta from a meliponary in Santarém, Pará state, in the region of the lower Amazonas River, in order to obtain data that can be used for the sustainable conservation of the bee species and flora in this Amazonian region. We analyzed, palinological analysis of 11 propolis samples collected from the meliponary and chemically only two (wet and dry season). For the melissopalynology, propolis was diluted in acetone and then applied to acetolysis. For a chemical evaluation were obtained hexane extracts from propolis samples April and August 2018 and analysis by gas chromatography coupled mass spectrometry. A multivariate analysis was performed with the pollen and chemical data. Seventy-seven pollen types were found, defining the propolis as heterofloral, with the families Fabaceae, Anacardiaceae and Myrtaceae being the most significant in the pollen spectrum of the samples. The most frequent species were: Copaifera martii, Eugenia brasiliensis, Mitracarpus strigosus, Protium heptaphyllum and Tamarindus indica. The hexane extracts of propolis had a 35.75% yield. Sixteen compounds were found and cycloartenol, lupeol acetate and lupenone were identified as major constituents.